Long term exposure to air pollution and mortality in an elderly cohort in Hong Kong. (August 2018) - Yang, Yang; Tang, Robert; Qiu, Hong; Lai, Poh-Chin; Wong, Paulina; Thach, Thuan-Quoc; Allen, Ryan; Brauer, Michael; Tian, Linwei; Barratt, Benjamin
Abstract: Background: Several studies have reported associations between long term exposure to air pollutants and cause-specific mortality. However, since the concentrations of air pollutants in Asia are much higher compared to those reported in North American and European cohort studies, cohort studies on long term effects of air pollutants in Asia are needed for disease burden assessment and to inform policy. Objectives: To assess the effects of long-term exposure to particulate matter with aerodynamic diameter < 2.5 μm (PM2.5 ), black carbon (BC) and nitrogen dioxide (NO2 ) on cause-specific mortality in an elderly cohort in Hong Kong. Methods: In a cohort of 66, 820 participants who were older than or equal to 65 years old in Hong Kong from 1998 to 2011, air pollutant concentrations were estimated by land use regression and assigned to the residential addresses of all participants at baseline and for each year during a 11 year follow up period. Hazard ratios (HRs) of cause-specific mortality (including all natural cause, cardiovascular and respiratory mortality) associated with air pollutants were estimated with Cox models, including a number of personal and area-level socioeconomic, demographic, and lifestyle factors. Results: The median concentration of PM2.5 during the baseline period was 42.2 μg/m 3 with an IQR of 5.5 μg/m 3, 12.1 (9.6) μg/m 3 for BC and 104 (25.6) μg/m 3 for NO2 . For PM2.5, adjusted HR per IQR increase and per 10 μg/m 3 for natural cause mortality was 1.03 (95%CI: 1.01, 1.06) and 1.06 (95%CI: 1.02, 1.11) respectively. The corresponding HR were 1.06 (95%CI: 1.02, 1.10) and 1.01 (95%CI: 0.96, 1.06) for cardiovascular disease and respiratory disease mortality, respectively. For BC, the HR of an interquartile range increase for all natural cause mortality was 1.03 (95%CI: 1.00, 1.05). The corresponding HR was 1.07 (95%CI: 1.03, 1.11) and 0.99 (95%CI: 0.94, 1.04) for cardiovascular disease and respiratory disease mortality. For NO2, almost all HRs were approximately 1.0, except for IHD (ischemic heart disease) mortality. Conclusion: Long-term exposure to ambient PM2.5 and BC was associated with an elevated risk of cardiovascular mortality. Despite far higher air pollution exposure concentrations, HRs per unit increase in PM2.5 were similar to those from recent comparable studies in North America. Highlights: Cohort studies on long term effects of exposure to high level air pollutants in Asia are needed Long-term exposure to PM2.5 and BC, but not NO2, was associated with cardiovascular mortality in a cohort of elderly adults. Hazard ratios for PM2.5 were similar to those in recent comparable studies in North America, despite higher exposure levels.